THE ANCIENT VERSIONS OF LAMENTATIONS - Van Rooy, H. F. (Scriptura, 2012)
The Ancient Versions of the Old Testament can be utilised for different purposes. Two of the most important usages of the Septuagint, Peshitta, Vulgate and the Targums are their use in the process of reconstructing the Hebrew text of the Old Testament and the reception of the Old Testament in different communities. This paper explores the value of the Ancient Versions of Lamentations in these two respects, discussing a representative number of examples. As far as the Hebrew text is concerned, the Ancient Versions were translated from a text close to the Masoretic Text. The Targum and Septuagint shed light on the reception of Lamentations in different Jewish communities, although the Septuagint was transmitted mainly in the Christian community. The Peshitta and Vulgate shed light on the reception in different Christian communities.